2020
DOI: 10.1111/hir.12327
|View full text |Cite
|
Sign up to set email alerts
|

Librarians collaborate successfully with nursing faculty and a writing centre to support nursing students doing professional doctorates

Abstract: This study explores how a three‐way collaboration between a University library, writing centre and faculty created avenues of training and support for students within a Doctor of Nursing Practice (DNP) program in an American University. The role of each partner involved in the collaboration is discussed alongside the profile of the DNP students. Lesson planning and classroom techniques for DNP information literacy classes are described and feedback from the partners and the students are discussed. The study co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Many studies have been conducted to investigate different aspects of embedded librarianship practice in academic libraries. They have often looked at the practice and impact of embedded librarianship in regards to library and information service provision to the students and staff (Alverson et al, 2019;Bernstein et al, 2020;Luca, 2019;Mensah and Owusu-Ansah, 2018;Shumaker, 2012;Tumbleson, 2016). Some studies (Bewick and Corrall, 2010;Brown et al, 2015;Chanetsa, 2014;Oyelude, 2013;Saunders, 2020) have partially examined librarians' skills and knowledge.…”
Section: Literature Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been conducted to investigate different aspects of embedded librarianship practice in academic libraries. They have often looked at the practice and impact of embedded librarianship in regards to library and information service provision to the students and staff (Alverson et al, 2019;Bernstein et al, 2020;Luca, 2019;Mensah and Owusu-Ansah, 2018;Shumaker, 2012;Tumbleson, 2016). Some studies (Bewick and Corrall, 2010;Brown et al, 2015;Chanetsa, 2014;Oyelude, 2013;Saunders, 2020) have partially examined librarians' skills and knowledge.…”
Section: Literature Gapmentioning
confidence: 99%
“…Existing literature suggests that librarians’ research skills and knowledge are key for the effective adoption of embedded librarianship in academic libraries. For example, librarians who have skills and knowledge in areas like proposal writing, data identification, information searching, and data management are qualified for embedded librarianship (Bernstein et al, 2020; Lawton and Burns, 2015; Mensah and Owusu-Ansah, 2018). In their exploration of embedded librarianship in a research context, Carlson and Kneale (2011) noted that ability to manage data, disseminate research findings beyond project personnel, and preserve data were some of the important embedded librarianship competencies that librarians used to interact with researchers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Librarian research and communication skills and knowledge are critical for librarians to provide excellent research support, collaborate with researchers and ensure the compelling success of embedded librarianship. For instance, librarians with high competencies in proposal writing, data identification and management and information searching in systematic reviews are highly qualified for adequate embedment in research (Bernstein et al ., 2020; Mensah and Owusu-Anasah, 2018). The study also found that librarians are skilled in research proposal writing, data analysis and various tools for analysing data, formulating hypotheses and designing and managing a research project.…”
Section: Competencies Of Librarians' Embeddedness In Researchmentioning
confidence: 99%
“…Available literature suggests graduate students need more knowledge, understanding, and ability to use scholarly resources to make sound clinical decisions 7. Similarly, DNP students have varying levels of IL, which contribute to anxiety when completing assignments that require research 8. Overall, more research on graduate nurses' IL must be conducted worldwide.…”
Section: Graduate Nursing Educationmentioning
confidence: 99%
“…However, only some studies indicate if a librarian was involved in instruction or curriculum design and development 6. Another study found that nursing faculty typically partner with a librarian through a liaison approach in which the librarian provides consultation but is not the primary faculty 8. In contrast, some suggest collaboration with librarians via modular integrated IL sufficiently improves IL competency 7…”
Section: Graduate Nursing Educationmentioning
confidence: 99%